Madrasas in 21st Century Indonesia and the Paradigm Shift in Curriculum Development - Masruji; Zaenuddin Hudi Prasojo; Wahab (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this article is to look at the paradigm of curriculum development in madrasas. The curriculum development should be able to answer the challenges and needs of 21st century learning. This type of research is qualitative with a literature study. Namely, by collecting various kinds of relevant scientific sources to be studied in depth regarding the topic of 21st century madrasas, as well as their development in Indonesia. The results of this study are; first, to face the challenges of the 21st century, madrasah education can relate to 4C-based PAI learning, critcal tingking, collaboration, communication, creativity. To prepare a generation that is superior, morally Islamic and able to compete both academically and non-academically. Second, the effective use of technology in 21st century Islamic Religious Education (PAI) learning can integrate smoothly. This is done by utilizing teaching platforms and various supporting media that support Islamic Education learning. The use of technology can enrich learning content, support discussion and cooperation among students, and provide wider access to various learning resources. Thus, students can more easily understand Islamic concepts, apply the values taught in daily life, and develop 21st century skills.